Thrombin-activatable fluorescent peptide incorporated gold nanoparticles for dual optical/computed tomography thrombus imaging. (January 2018) - Kwon, Sung-Pil; Jeon, Sangmin; Lee, Sung-Hoon; Yoon, Hong Yeol; Ryu, Ju Hee; Choi, Dayil; Kim, Jeong-Yeon; Kim, Jiwon; Park, Jae Hyung; Kim, Dong-Eog; Kwon, Ick Chan; Kim, Kwangmeyung; et al.
Abstract: Thrombosis is an important pathophysiologic phenomenon in various cardiovascular diseases, which can lead to oxygen deprivation and infarction of tissues by generation of a thrombus. Thus, direct thrombus imaging can provide beneficial in diagnosis and therapy of thrombosis. Herein, we developed thrombin-activatable fluorescent peptide (TAP) incorporated silica-coated gold nanoparticles (TAP-SiO2 @AuNPs) for direct imaging of thrombus by dual near-infrared fluorescence (NIRF) and micro-computed tomography (micro-CT) imaging, wherein TAP molecules were used as targeted thrombin-activatable peptide probes for thrombin-specific NIRF imaging. The freshly prepared TAP-SiO2 @AuNPs had an average diameter of 39.8 ± 2.55 nm and they showed the quenched NIRF signal in aqueous condition, due to the excellent quenching effect of TAP molecules on the silica-gold nanoparticle surface. However, 30.31-fold higher NIRF intensity was rapidly recovered in the presence of thrombin in vitro, due to the thrombin-specific cleavage of quenched TAP molecules on the gold particle surface. Furthermore, TAP-SiO2 @AuNPs were successfully accumulated in thrombus by their particle size-dependent capturing property, and they presented a potential X-ray absorption property in a dose-dependent manner. Finally, thrombotic lesion was clearly distinguished from peripheral tissues by dual NIRF/micro-CT imaging after intravenous injection of TAP-SiO2 @AuNPs in the in situ thrombotic mouse model, simultaneously. This study showed that thrombin-activatable fluorescent peptide incorporated silica-coated gold nanoparticles can be potentially used as a dual imaging probe for direct thrombus imaging and therapy in clinical applications.